HUBUNGAN TENSION TYPE HEADACHE DENGAN TINGKAT KEPARAHAN INSOMNIA - Maria Lawrensia Tampubolon,* Herlina Suryawati,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION INSOMNIA IS ONE OF THE MOST COMMON SLEEP DISORDERS INSOMNIA CAN BE CAUSED BY A MEDICAL DISORDER OR COMORBID ONE OF THEM IS HEADACHE INSOMNIA OFTEN ASSOCIATED WITH TENSION TYPE HEADACHE TTH A PRIMARY HEADACHE CAN BE A COMPLICATION IN THE TREATMENT OF TTH